Effects of different conditioning activities on the sprint performance of elite sprinters: A systematic review with meta-analysis - Loturco, I.; Pereira, L. A.; Moura, T. B. M. A.; McGuigan, M. R.; Boullosa, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose Postactivation performance enhancement (PAPE), which refers to the phenomena associated with the attainment of enhanced performance in sport-specific tasks after a conditioning activity, is an important objective of warming-up practices in many sports. This is even more relevant for sprinters, as potential increases in sprinting speed will directly influence their competitive results. This systematic review with meta-analysis evaluated the effects of different PAPE protocols (ie, using plyometrics, strength-power exercises, and resisted/assisted sprints) on the sprinting performance (ie, sprint time or sprint speed) of competitive sprinters.